Editorial: Special Edition on Banking, Competition & Corporate Law: Confronting Contemporary Challenges of Banking, Competition & Corporate Law to Enhance Consumer Protection - Chitimira, Howard (Potchefstroom Electronic Law Journal, 2024)
Although Zimbabwe has established several institutions to combat money laundering and related crimes, there is a perception that inadequate measures are taken to apprehend offenders responsible for financial crimes. Institutions such as the Financial Intelligence Unit (FIU), the Zimbabwe Anti-Corruption Commission (ZACC), the Zimbabwe Republic Police (ZRP), the National Prosecuting Authority (NPA) and the Reserve Bank of Zimbabwe (RBZ) have done little to prove that the government of Zimbabwe is resolute in combatting money laundering. On the contrary, it increasingly appears that these institutions are poorly equipped and lack the necessary capacity to enforce and uphold anti-money laundering (AML) measures in Zimbabwe. Further, there appears to be a selective application of the law, with one set of rules for individuals or institutions that are perceived as political adversaries of the incumbent establishment and a different set of rules for the political elite. Consequently, the selective application of the law projects Zimbabwe as a jurisdiction that is somehow tolerant to money laundering, corruption and related financial crimes, thereby lowering and tarnishing the standing of the country in the global economic community of nations. This paper provides a regulatory analysis of the AML role-players in Zimbabwe in order to assess their functions in combatting financial crimes. It also analyses whether these role-players are effective and substantively executing their responsibilities therein. The authors argue that while Zimbabwe is well able to effectively combat money laundering through the even application of the law to all persons regardless of their political or economic standing, it is imperative that its AML institutions operate without fear, favour or prejudice. This is crucial in combatting money laundering and instilling confidence in the general public's perception of AML institutions in Zimbabwe.
Keywords: Banking; Competition; Financial crimes; Financial markets; Securities

Antitrust policy and EU labour markets : lessons from the US and comparative prospects - Langlois D'estaintot, Isaure (European University Institute, 2024)
Recent empirical evidence suggests that labour markets are not as competitive as previously thought. In that context, mobilizing antitrust policy has been discussed as a possible solution. The proposition sounds counterintuitive, however. If workers are paid below the competitive level, doesn’t this promote consumers’ outcomes by reducing downstream prices? Given that antitrust policy promotes consumer welfare, why would antitrust authorities intervene against such a state of affairs? Besides, why would stepping up on antitrust enforcement improve workers’ outcomes? Their interests have traditionally been protected through their exclusion from the scope of antitrust enforcement, not by the enforcement of antitrust rules to their benefit. This thesis demonstrates that those spontaneous assumptions do not hold. Consumer welfare does not speak against the defence of workers’ interests. First, the focus on consumers is a by product of methods: it does not prevent consideration of other types of market participants. Moreover, consumers benefit from competitive labour markets. The welfare effects of monopsony power simultaneously worsen workers and consumers’ outcomes. As for the promotion of workers’ interests, it can be achieved through both positive and negative enforcement of antitrust. So far, the EU Commission has been less proactive than the American DOJ and FTC on the issue of antitrust enforcement in labour markets ( although the state of affairs is evolving). While this difference may stem from EU workers benefitting from higher levels of social protection than US workers, those higher levels of protection may not negate the usefulness of antitrust ’s intervention. The low levels of antitrust enforcement in EU labour markets may result from legal uncertainty and case law inconsistency more than an absence of harm. Just like the merger control apparatus, Article 101 and 102 TFEU can be used to scrutinize labour markets. While doing so involves some practical complexities, they can be overcome.
Keywords: Antitrust law; European Union countries; Labor laws and legislation; Unfair competition